Bloodstained sea the U.S. Coast Guard in the Battle of the Atlantic, 1941-1944 - Walling, Michael G. (International Marine/McGraw-Hill, 2004)
"In November 1941 America was not yet officially at war. Nevertheless, under orders from President Roosevelt, sailors of the U.S. Coast Guard painted their gleaming white cutters battleship gray and steamed into action against the menacing U-boats of the Third Reich. Bloodstained Sea recounts how, over the next four years, these men - normally dedicated to saving lives and rescuing ships in distress - would be locked in one of the longest and bloodiest running sea battles in history."